Data Sharing to Inform School‐Based Asthma Services. (December 2013) - Portwood, Sharon G.; Nelson, Elissa B.
ABSTRACT: BACKGROUND: This article examines results and lessons learned from a collaborative project involving a large urban school district, its county health department, multiple community partners, and the local university to establish an effective system for data sharing to inform monitoring and evaluation of the Charlotte Mecklenburg Schools (CMS) Asthma Education Program (AEP). METHODS: Databases maintained by nurses, program staff, and school personnel were integrated into a single AEP Evaluation Database. RESULTS: There were a number of positive findings, including evidence that students with an elevated level of need received priority from AEP. A series of dependent group t tests analyzing changes across time in students' grade‐point averages and absences, as well as their implications, also demonstrated some improvements. Additional outcome analyses for the 296 students who received case management services demonstrated further program benefits in the areas of attendance, academic performance, behavior, and quality of life. CONCLUSIONS: Enhancing the ability of school‐based programs to merge data across project partners will facilitate efforts not only to evaluate services but also to demonstrate program impact on a wide variety of health and academic outcomes for students.